(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The main difficulty is still determining the appropriate soil stabilizers to overcome the challenges posed by soft soils, not only in terms of achieving the required soil engineering features but also in terms of cost and environmental effect. The purpose of this paper was to look at the soil stabilization technologies that had been created via experiments. The effectiveness of hydroxide solution additive, fly ash terpolymeric cement, various ashes, and cementitious binders for soil stabilizers were all examined. Based on compressive strengths (UCS) or California Bearing Ratio (CBR) tests, the performance of these materials for supporting soft soils was determined purely in terms of strength. These chemicals significantly increased the strength of the soft ground, indicating that they may be used as effective soil stabilizers in the field